Involvement of Catholic Young People in the Koinonia Field - Trinovena Br Manjorang; Abdi Guna Sitepu; Erikson Simbolon (Journal of Education Technology Information Social Sciences and Health, 2024)
This article aims to understand the level of involvement of Catholic youth in the field of koinonia and to formulate strategies to increase their participation. Catholic youth, aged between 13 and 35 years and unmarried, play a crucial role in the development of the Catholic Church and are responsible for the sanctification of life and active participation in fellowship. However, the phenomenon shows that many young Catholics are losing interest in church activities and tend to be more attracted to worldly activities than spiritual ones. This creates a challenge in maintaining their engagement in the field of koinonia (fellowship). In this article, the author employs a qualitative approach, reviewing books and journals to elaborate on the content to be discussed. The results of this research indicate that the presence of Catholic youth in koinonia activities is very minimal, though their involvement in each activity is already active. Therefore, Catholic youth still need encouragement to increase their attendance in every Introduction group prayer activity, recollection, liturgical celebration, catechesis, and leadership training.